Teaching Interculturally 'Otherwise' - dervin, fred; Yuan, Mei; Sude (Taylor & Francis, 2023)
This edited volume focuses on the thorny and somewhat controversial issue of teaching (and learning) interculturality in a way that considers the notion from critical and reflexive perspectives when introduced to students. Comprised of three parts, the book discusses the nuts and bolts of teaching interculturally, considers changes in the teaching of interculturality, and provides pedagogical insights into interculturalising the notion. It studies both teaching im-/explicitly about interculturality and how to incorporate interculturality into teaching practices or into an institution. By sharing varied cases and theoretical reflections on the topic, the editors and contributors from different parts of the world aim to stimulate more initiatives to enrich the field instead of delimiting it, especially in complement to and beyond the 'West' or 'Global North', and also to build up further reflexivity in the way readers engage with interculturality in education. This will be a must-read for teachers and researchers of intercultural communication education at different educational levels, as well as anyone interested in scholarship on education for interculturality.